Potencial ecotoxicológico e atividade antihelmíntica in vitro de cnidoscolus quercifolius pohl (euphorbiaceae) sobre nematoides gastrintestinais de ovinos - Felix, Renata Cristinne da Silva (Universidade Federal Rural do Semi-Árido, 2021)
The small ruminant rearing in Brazil is considered a profitable and promising activity in the agriculture. However, the rearing of herds is made difficult due to the parasitic diseases that affect the animals. Commercialized chemical antiparasitic drugs are the fastest and most practical way to control gastrointestinal parasites; however, incorrect handling, the excessive use of anthelmintics and the weather conditions at the region favor the development of parasite resistance. So, an alternative to chemical treatment is phytotherapy, which highlights the species Cnidoscolus quercifolius (Pohl), popularly used in wound healing, pain and inflammation, in addition to diuretic action, but still without proven effect against parasites. So, the aim of the study was to analyze in vitro the ovicidal action and ecotoxicity of the aqueous extract obtained from the leaves of C. quercifolius and to analyze the phytochemical components of the leaf. For this, five collections of fecal samples were carried out in a sample pool of 10% of a sheep herd. Subsequently, the hatchability test was carried out using the technique of recovering eggs in animal feces, followed by the analysis of acute ecotoxicity in planktonic crustacean species Daphnia magna and the phytochemical tests. The results showed that the extract has inhibitory activity on egg hatching, showing 100% inhibition in all concentrations used (10%, 5%, 2.5% and 1.25%). As for the acute ecotoxicity test, the extract of C. quercifolius was toxic, immobilizing 100% of the organisms at the four concentrations tested, doing the chronic test unnecessary. The phytochemical analysis showed the presence of phenols, flavonoids, condensed tannins, saponins, alkaloids and triterpenes, which may be related to the ovicidal action of the extract. So, it was concluded that the aqueous extract of C. quercifolius has antiparasitic activity and has proven secondary metabolites, however, it proved to be toxic. Therefore, the aqueous extract obtained from C. quercifolius it needs studies at lower concentrations, which reduce its ecotoxicity and find an effective dose for the treatment of small ruminants
Keywords: Ovinocultura; Resistência parasitária; Ecotoxicidade; Fitoterápico; Sheep farming; Parasitic resistance; Ecotoxicity; Phytotherapy; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE